Synergistic effect of chemical and bio-based surfactants in stabilizing nanoemulsions - Nansee S.K. Abu Zaid (22986676) (2025)
In response to the increasing need for versatile and eco-friendly emulsion systems across various industries, this study investigates the synergistic effects of bio-based Rhamnolipids (RLs) and synthetic nonionic Tween 40 surfactants in stabilizing diesel-in-water nanoemulsions. To the best of our knowledge, nanoemulsions stabilized by a combination of bio-based and chemical surfactants are scarce in existing literature. The concentration of Tween 40 was adjusted to 0.02, 0.1, 0.5, and 1.0 wt%, with a minimal RLs dosage of 0.004 wt%. This novel bio/chemical surfactant blend resulted in stable nanoemulsions with superior characteristics compared to those stabilized by either surfactant alone. The prepared nanoemulsions were systematically evaluated against those formulated with individual emulsifiers in terms of stability, droplet size, zeta potential, interfacial tension, morphology, and rheological properties. Including RLs in the nanoemulsion formulations enhanced emulsion stability increased zeta potential and significantly lowered dynamic interfacial tension. Rheological assessments demonstrated the nanoemulsions' shear-thinning behavior and their predominantly viscous nature (G'' > G′), reflecting a fluid-like response under stress. Temperature-dependent analyses provided valuable insights into the nanoemulsions' flow and stability, particularly by determining the activation energy required for flow, emphasizing their sensitivity to temperature variations and thermal resilience. The application of various rheological models, including Ostwald-de Waele, Bingham, and Herschel-Bulkley, enabled a thorough understanding of the nanoemulsions' behavior under diverse conditions. The attractive characteristics of the nanoemulsions, especially those containing trace amounts of RLs, suggest promising applications in oilfield operations and other industrial sectors. Other Information Published in: Geoenergy Science and Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.geoen.2025.213663